Analisis Tata Ruang Dalam Kenyamanan Kerja dan Opimalisasi Kinerja pada Bank Muamalat KCU Medan Baru - Arif Ramadhan; Nurul Jannah (Economic Reviews Journal, 2022)
This study aims to determine (1) : office space management that has been carried out at Bank Muamalat Kcu Medan Baru (2) Achievements and efforts in the problem of employee comfort at Bank Muamalat Kcu Medan Baru. (3) the existing management plan of Bank Muamalat Kcu Medan Baru on effective spatial management. The data collection technique is qualitative with descriptive method. The data obtained at Bank Muamalat Kcu Medan Baru there are several errors and obstacles in the arrangement of the room so that some good strategies are needed so that the company maximizes the arrangement in accordance with the principles of spatial management so that the company is comfortable and the employees work well. Keywords: Office Layout, Work Comfort, Employee Performance